Economically effective and ecologically reasonable way of band seedig - Ya. P. Lobachevskiy; B. Kh. Akhalaya; O. A. Sizov; V. B. Lovkis (Сельскохозяйственные машины и технологии, 2015)
Use of band seeding can be one of effective ways of achievement of this purpose. The authors developed a special pneumatic sowing device for simultaneous seeding of seeds of two crops in one row. The chosen for experiment cultures, soy and maize, have seeds with various size. A pneumatic system for service of two dosing elements was equipped with additional branch pipes, pneumatic seed ejector blade is applied instead of a metal one, so seeds damage eliminates. A disk created for simultaneous sowing of seeds of two crops has two pieces. Their moving relatively each other allows sowing scheme changing without replacement of disks. Key parameters of the sowing device should be determine to provide guaranteed filling of conic cells of the sowing disk and achievement of non-stop operation of the dosing system. Seeds feeding angle for conic cells equals 20-30 degrees. For a guaranteed filling of cells with seeds, length of the basis of a dejection cone should to be 60-80 mm, the relation of quantity of the seeds, which are taken out by a disk on a tape to number of disk turns equals 1.2-1.6 that depends on culture type. For soy with a small seeds, this indicator is less than 1.6. Corn seeds have smaller mobility of seeds and higher unevenness of process of filling of cells, so it is equal 1.4. It is possible to correct the sizes of the sowing device depending on a sowed culture. A seeds saving makes 20-30 percent.